2005
DOI: 10.1210/jc.2005-0803
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cortisol Biosynthesis Decreases Circulating Leptin Levels in Obese Humans

Abstract: We conclude that metyrapone-induced inhibition of cortisol biosynthesis results in hypoleptinemia, which indicates that glucocorticoids may play an important role in the physiological regulation of leptin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
15
1
1
Order By: Relevance
“…It has been shown that short-term administration of glucocorticoids increases leptin secretion (36)(37)(38)(39), whereas long-term intrinsic glucocorticoid excess such as in patients with Cushing's syndrome has no effect on leptin levels (40). DagogoJack et al demonstrated that a metyrapone-induced inhibition of cortisol biosynthesis results in hypoleptinemia (41). In our cohort, we did not find any association of the leptin axis with equivalent HC dosage or the used glucocorticoid.…”
Section: Discussioncontrasting
confidence: 57%
“…It has been shown that short-term administration of glucocorticoids increases leptin secretion (36)(37)(38)(39), whereas long-term intrinsic glucocorticoid excess such as in patients with Cushing's syndrome has no effect on leptin levels (40). DagogoJack et al demonstrated that a metyrapone-induced inhibition of cortisol biosynthesis results in hypoleptinemia (41). In our cohort, we did not find any association of the leptin axis with equivalent HC dosage or the used glucocorticoid.…”
Section: Discussioncontrasting
confidence: 57%
“…Leptin has been shown to have pleiotropic effects in regulating appetite, fat metabolism, growth, reproduction, body temperature, bone remodeling, immune function, stress, inflammatory responsiveness, hematopoiesis and angiogenesis (Steppan et al 2000;Dagogo-Jack et al 2005;Swoap 2008;Friedman 2009;Lafrance et al 2010;Copeland et al 2011). Notably, because of the tremendous differences in gene sequence, studies of leptin in fish lag behind studies in mammals significantly (Copeland et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…They are chronically obese, hyperphagic, hypothermic, and do not sexually mature; injections of leptin rescues all of these phenotypes. Leptin has demonstrated effects in regulating appetite, fat metabolism, reproduction, body temperature, growth, bone remodeling, immune function, stress, inflammatory responsiveness, hematopoiesis, and angiogenesis (Pelleymounter et al, 1995; Barash et al, 1996; Bennett et al, 1996; Grunfeld et al, 1996; Fruhbeck et al, 1997; Sierra-Honigmann et al, 1998; Steppan et al, 2000; Dagogo-Jack et al, 2005; Lafrance et al, 2010; and reviewed in Swoap, 2008; Friedman, 2009). Its pleiotropic effects and its potential for treating obesity have resulted in >28,000 published studies to date (ISI).…”
Section: Leptin As An Integrating Signal In Mammalsmentioning
confidence: 99%